Determinants of Diarrhea Incidence Among Infants: The Role of Maternal Education, Health Information, Exclusive Breastfeeding and Nutritional - Nurun Nikmah; Selvia Nurul Qomary; Nurul Jannatul Wahidah; Hamimatus Zainiyah; vivin wijiastutik (JURNAL INFO KESEHATAN, 2026)
Infant diarrhea presents a series of health challenges, including loss of appetite, electrolyte disturbances, undernutrition, increased vulnerability to other infections, and potential delays in physical and cognitive development. This study aimed to examine the determinants influencing the occurrence of diarrhea among infants aged 6–12 months at Independent Clinic of Midwife Meiyuni, S.ST., Bd. The variables explored were maternal educational attainment, exposure to health-related information, exclusive breastfeeding history, and the infant’s nutritional status. A cross-sectional analytical approach was employed using a total sampling technique involving 55 infants. Bivariate analysis was conducted through simple logistic regression. The results revealed significant associations of maternal education (R² = 33.7%, F = 26.905, p = 0.001), maternal access to health information (R² = 28.7%, F = 21.302, p = 0.001), exclusive breastfeeding history (R² = 57.6%, F = 71.980, p = 0.001), and nutritional status (R² = 55.8%, F = 66.836, p = 0.001) on the incidence of diarrhea. These research findings highlight the importance of improving maternal education and health literacy, promoting exclusive breastfeeding, and enhancing children’s nutritional status as key strategies for preventing diarrhea through effective preventive interventions.